Modeling of mullite solid-solutions in the system Al2O3-SiO2 - Holm J.L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A model for the mullite formation from kaolinites and the solid-solution range of mullite in the Al2O3-SiO2 system has been evaluated. This rather complicated model implies that both octahedral and tetrahedral coordinated Al3+-ions as well as tetrahedral Si4+-ions participate together with O2-ions and vacant oxygen positions during the rearrangements in the structure during the sintering process at high temperatures.